There Is No Immersion: Critical Intervention through Hypermediacy in Metagames - Thorne, Sarah (Eludamos: Journal for Computer Game Culture, 2021)
In 2020, Draw Me a Pixel released There Is No Game, a game that playfully engages with the concept of the metagame and its varied meanings to examine the relationship between developers, games, and their audiences. The game has much in common with other metagames released during the boom and bust cycle of the indie game market in terms of its themes and playful attitude toward its players. Like many of these games, it features an antagonistic narrator, who, upon launching the game, announces that there is no game. The concept of a game resistant to play has become a recurring theme in many metagames that critique industry pressures, trends, and players’ playful resistance to designed experiences. This article examines There Is No Game’s use of hypermediacy (as a feature of both its narrative and design) to deliver its critique of the industry, while offering insight into its own development. More than simply breaking the fourth-wall, hypermediacy becomes the instigator for critical reflection and is used to highlight the challenges faced by indie developers and the material conditions in which games are made. Yet, unlike its predecessors that share this critique, There Is No Game offers an optimistic perspective on the future of the industry.